2007
DOI: 10.1097/smj.0b013e31802fa2a8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ankylosing Spondylitis with Moxifloxacin

Abstract: Ankylosing spondylitis (AS) is a human leukocyte antigen (HLA)-B27-associated chronic inflammatory disease of unknown etiology. There are few effective treatments for ankylosing spondylitis, which causes substantial morbidity. The relationship between AS and enterobacteria, especially Klebsiella pneumoniae, has been reported from several groups in several countries. We performed an open-label trial of moxifloxacin, a fluoroquinolone antibiotic, in patients with ankylosing spondylitis. Treatment with moxifloxac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Given the fact that oral bacteria could contribute to the aetiology of rheumatic diseases, it is conceivable that the adjuvant administration of antibiotics could represent a strategy in addition to scaling and root planing to improve the therapeutic outcome of rheumatic disease. Therapeutically positive effects for antibiotics were already proven in particular for disease‐modifying, antirheumatic drug‐resistant rheumatic diseases (Ogrendik ,b,c, , Ogrendik & Karagoz ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the fact that oral bacteria could contribute to the aetiology of rheumatic diseases, it is conceivable that the adjuvant administration of antibiotics could represent a strategy in addition to scaling and root planing to improve the therapeutic outcome of rheumatic disease. Therapeutically positive effects for antibiotics were already proven in particular for disease‐modifying, antirheumatic drug‐resistant rheumatic diseases (Ogrendik ,b,c, , Ogrendik & Karagoz ).…”
Section: Discussionmentioning
confidence: 99%
“…Moxifloxacin is a fluoroquinolone antibiotic with activities against both Gram-positive and -negative bacteria. The results of a similar study have shown that AS patients treated with Moxifloxacin resulted in a significant and sustained improvement and the mean of erythrocyte sedimentation rate and C-reaction protein decreased significantly after 12 weeks [108]. It was also noticed that some South African plant extracts with K. pneumoniae inhibitory activity can potentially prevent the AS onset and minimize the symptoms of the established disease [109].…”
Section: Intestinal Microbiome Targeting Strategiesmentioning
confidence: 99%
“…Although the cross reactivity between HLA-B27 and Klebsiella antigens has been put forward in many publications, this cross reactivity has not been shown [21]. …”
Section: Hypothesismentioning
confidence: 99%
“…HLA-B27 is present on antigen-presenting cells, and it presents endogenous peptides to CD8 (+) T-cells [21]. The arthritogenic peptide hypothesis postulates that B27 plays a direct role in pathogenesis by binding an arthritogenic peptide and presenting it to autoreactive CTLs [22].…”
Section: Hypothesismentioning
confidence: 99%